Systematic review and meta-analysis of intravascular temperature management vs. surface cooling in comatose patients resuscitated from cardiac arrest. (1st January 2020) - Bartlett, Emily S.; Valenzuela, Terence; Idris, Ahamed; Deye, Nicolas; Glover, Guy; Gillies, Michael A.; Taccone, Fabio S.; Sunde, Kjetil; Flint, Alexander C.; Thiele, Holger; Arrich, Jasmin; Hemphill, Claude; et al.
Abstract: Objective: To systematically review the effectiveness and safety of intravascular temperature management (IVTM) vs. surface cooling methods (SCM) for induced hypothermia (IH). Methods: Systematic review and meta-analysis. English-language PubMed, Embase and the Cochrane Database of Systematic Reviews were searched on May 27, 2019. The quality of included observational studies was graded using the Newcastle-Ottawa Quality Assessment tool. The quality of included randomized trials was evaluated using the Cochrane Collaboration's risk of bias tool. Random effects modeling was used to calculate risk differences for each outcome. Statistical heterogeneity and publication bias were assessed using standard methods. Eligibility: Observational or randomized studies comparing survival and/or neurologic outcomes in adults aged 18 years or greater resuscitated from out-of-hospital cardiac arrest receiving IH via IVTM vs. SCM were eligible for inclusion. Results: In total, 12 studies met inclusion criteria. These enrolled 1573 patients who received IVTM; and 4008 who received SCM. Survival was 55.0% in the IVTM group and 51.2% in the SCM group [pooled risk difference 2% (95% CI −1%, 5%)]. Good neurological outcome was achieved in 40.9% in the IVTM and 29.5% in the surface group [pooled risk difference 5% (95% CI 2%, 8%)]. There was a 6% (95% CI 11%, 2%) lower risk of arrhythmia with use of IVTM and 15% (95% CI 22%, 7%) decreased risk of overcooling with use of IVTM vs. SCM. There was no significant difference in other evaluated adverse events between groups. Conclusions: IVTM was associated with improved neurological outcomes vs. SCM among survivors resuscitated following cardiac arrest. These results may have implications for care of patients in the emergency department and intensive care settings after resuscitation from cardiac arrest.